2021
DOI: 10.3389/fimmu.2021.622537
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Mirtazapine Rapidly Shifts Hepatic B Cell Populations and Functional Cytokine Signatures in the Mouse

Abstract: IntroductionB cells are important regulators of both adaptive and innate immunity. The normal liver contains significant numbers of B cells, and their numbers increase dramatically in immune-mediated liver diseases. Our previous observations suggest a hepatoprotective effect of the antidepressant mirtazapine in human and experimental immune-mediated liver disease. Therefore, we performed a series of experiments to determine the impact of mirtazapine treatment on hepatic B cell homeostasis, as reflected by B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…CXCR3 and CXCR4 were previously reported to be expressed by non-B lymphocyte immune cells and related to retention in the liver ( 26 ). Recent studies showed that CXCR3 and CXCR4 can also be expressed on B cells ( 27 , 28 ). Our study demonstrated that CXCR3 was highly expressed on TSPAN1 + B cells.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 and CXCR4 were previously reported to be expressed by non-B lymphocyte immune cells and related to retention in the liver ( 26 ). Recent studies showed that CXCR3 and CXCR4 can also be expressed on B cells ( 27 , 28 ). Our study demonstrated that CXCR3 was highly expressed on TSPAN1 + B cells.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Almishri and colleagues ( 44 ) have shown that treatment of mice with mirtazapine leads to shifting towards B1 B cells in the liver. It is conceivable that this might elevate hepatic nIgM titers exerting positive effects on liver immune homeostasis.…”
Section: Mirtazapine Enriches B1 B Cells In the Liver: A Beneficial R...mentioning
confidence: 96%
“…The atypical antidepressant, mirtazapine, shows antagonistic effects on several receptors including histamine receptor H1 ( 42 ) and serotonin receptors 5HT3 and 5HT3A ( 43 ) expressed by B cells. Almishri and colleagues ( 44 ) reported that mice treated with mirtazapine showed a drastic reduction of overall B cell numbers in the liver. In particular, remaining liver-localized B cells were skewed towards B1 B cells.…”
Section: Mirtazapine Enriches B1 B Cells In the Liver: A Beneficial R...mentioning
confidence: 99%
See 2 more Smart Citations